An analog of Hardy’s theorem for the second Hankel-Clifford transformation (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this paper, we generalize theorem of Hardy for the second Hankel-Clifford transform .
Keywords: econd Hankel-Clifford transformation; Bessel-Clifford function